2015
DOI: 10.1099/mic.0.000067
|View full text |Cite
|
Sign up to set email alerts
|

New insight into the photoheterotrophic growth of the isocytrate lyase-lacking purple bacterium Rhodospirillum rubrum on acetate

Abstract: Purple non-sulfur bacteria are well known for their metabolic versatility. One of these bacteria, Rhodospirillum rubrum S1H, has been selected by the European Space Agency to ensure the photoheterotrophic assimilation of volatile fatty acids in its regenerative life support system, MELiSSA. Here, we combined proteomic analysis with bacterial growth analysis and enzymatic activity assays in order to better understand acetate photoassimilation. In this isocitrate lyaselacking organism, the assimilation of two-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(82 citation statements)
references
References 54 publications
7
75
0
Order By: Relevance
“…This could be explained by the fact that at high oxygen concentration (∼21%), this photoheterotrophic bacterium would lack photosynthetic complexes and uses aerobic respiration for energy generation (Zeller et al, 2005) due to a high sensitivity of PS to oxidative damage (Nishiyama et al, 2005). Light-regulated metabolic versatility in this photoheterotrophic strain could also be observed in a down-regulation of the enzyme acetyl-coA synthetase (RH2_00279, ratio = 0.66, UVA+UVB condition), involved in acetate assimilation, indicating that during the PAR light condition (used as control), this alternative pathway would have an important role in anabolic processes (Imam et al, 2013; Leroy et al, 2015). …”
Section: Discussionmentioning
confidence: 78%
“…This could be explained by the fact that at high oxygen concentration (∼21%), this photoheterotrophic bacterium would lack photosynthetic complexes and uses aerobic respiration for energy generation (Zeller et al, 2005) due to a high sensitivity of PS to oxidative damage (Nishiyama et al, 2005). Light-regulated metabolic versatility in this photoheterotrophic strain could also be observed in a down-regulation of the enzyme acetyl-coA synthetase (RH2_00279, ratio = 0.66, UVA+UVB condition), involved in acetate assimilation, indicating that during the PAR light condition (used as control), this alternative pathway would have an important role in anabolic processes (Imam et al, 2013; Leroy et al, 2015). …”
Section: Discussionmentioning
confidence: 78%
“…PFOR catalyses the reverse carboxylation of acetyl‐CoA to generate pyruvate and the rate of the reaction depends exclusively on the concentration of acetyl‐CoA and pyruvate. PFOR activity is expected to be stimulated in the presence of acetate in the cultures (Leroy et al ., ). A control experiment was performed with cells growing in the presence of acetate 30 mM showing that this step is functional in these growth conditions (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…rubrum. We demonstrated that the duration of the lag phase is linked with inoculum size, suggesting that high light intensity could be deleterious to diluted cells (Leroy et al, 2015). We proposed that high light intensity, resulting from the dilution of the cells at inoculation, could result in an intracellular imbalance in the cofactor pool.…”
Section: Introductionmentioning
confidence: 94%
“…It is now well accepted that in organisms lacking isocitrate lyase gene (icl − ) (Kornberg and Krebs, 1957), such as Rs. rubrum, an alternative pathway is used for acetate assimilation (i.e., the ethylmalonyl-CoA pathway) (Leroy et al, 2015). In addition to this pathway, the implication of other pathways in acetate photoheterotrophic assimilation has been proposed, and further studies are still needed to attest their possible involvement in acetate assimilation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation